Impact of Hard Palate Angulation Caused by Septal Deviation on Maxillary Sinus Volume - Sapmaz, Emrah; Kavakli, Ahmet; Sapmaz, Hilal Irmak; Ogeturk, Murat (Galenos Yayincilik, 2018)
Objective: To investigate the effect of hard palate angulation caused by septal deviation on the volume of the maxillary sinus. Methods: Coronal computed tomographic (CT) scans of 1568 patients aged from 18 to 60 were examined. CT scans of 402 patients were included in the study. On these scans, the maxillary sinus volume, the angle of the nasal septal deviation, and the angulation of the hard palate were calculated using the ImageJ software. Each maxillary sinus volume was statistically compared with each other and with those in the control group. Correlations between palatal angulation and septal deviation were determined. Results: Deviated nasal septum whether with or without deflection of the hard palate was noted to have caused changes in the volume of the maxillary sinus in both female and male patients. The volume of the maxillary sinus on the deviated side was less than that of the opposite side, and the differences between the volumes of both sinuses were statistically significant (p<0.05). No significant differences were noted when compared with the control group. A positive correlation was observed between the nasal septal deviation angle and the angulation of the hard palate. Conclusion: Regardless of whether or not it affects the hard palate, nasal septal deviation reduces the volume of the maxillary sinus on the deviated side but does not affect the total volume of the maxillary sinuses. Significant differences between the volumes on the two sides can lead to facial asymmetry.
Keywords: Nasal septal deviation; hard palate; maxillary sinus; computed tomography